Mechanochemical grinding method for efficiently degrading PFAS

Through the mechanochemical grinding method of B4C as a ball milling additive, the C-F bond in PFAS is interrupted and the B-F bond is formed, which solves the efficient degradation problem of PFAS pollution and achieves rapid degradation and environmentally safe treatment effects.

CN119258479APending Publication Date: 2025-01-07CHINESE RES ACAD OF ENVIRONMENTAL SCI
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411381942.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In the prior art, when dealing with PFAS pollution, high-temperature incineration methods generate toxic gases, landfills lead to soil and groundwater pollution, and lacks efficient, low-cost and secondary pollution-free degradation methods.

Method used

B4C is used as a ball mill additive, and B4C and PFAS are ground in a ball mill by mechanochemical grinding method. The high-energy free electrons on the surface of B4C interrupt the C-F bond in PFAS to form a B-F bond to realize the degradation of PFAS, and the ball mill is adjusted. The shape and structural modification of speed, filling rate and B4C are optimized to optimize the grinding conditions.

Benefits of technology

The rapid degradation of PFAS is achieved, the release of F is reduced, environmental pollution is avoided, and oxidants, high temperature and high pressure and harmful additives are not required, reducing potential harm to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258479A_ABST
    Figure CN119258479A_ABST
Patent Text Reader

Abstract

The invention discloses a mechanochemical grinding method for efficiently degrading PFAS, which comprises the following steps: adopting B4C as a ball milling aid, putting B4C and PFAS into a ball mill according to a mass ratio of (250-1000): 50, and grinding until B-C bonds in B4C are broken, C-F bonds in PFAS are broken and B-F bonds are formed, thereby completing the degradation of PFAS; according to the method, the grinding process is improved through B4C, free electrons can be generated in the grinding treatment process, then PFAS is degraded, and the method has the advantages of being low in cost, high in efficiency and free of secondary pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of PFAS degradation, and in particular to a mechanochemical grinding method for efficiently degrading PFAS. Background Art

[0002] Perfluorinated / polyfluorinated compounds (PFAS) are widely used as fluorinated surfactants. PFAS are usually present in environmental media such as solid waste, soil and sediment, and then exposed to humans and ecological receptors at all stages of their life cycle, seriously threatening human health and the ecological environment. The global solid waste management industry urgently needs new technologies to solve the serious pollution problem of PFAS in environmental media such as solid waste, soil and sediment.

[0003] Existing technologies use methods such as incineration and thermal desorption to treat the problem. High-temperature incineration produces toxic and harmful gases during the incineration process, such as CF 4 , C 2 F 4 Landfill is another modern method for disposing PFAS-containing solid waste, which cannot decompose PFAS in the environment but leads to further soil and groundwater contamination. Therefore, it is urgent to develop comprehensive and environmentally friendly disposal technologies to treat PFAS in solids.

[0004] There are few reports on the degradation of PFAS by mechanical ball milling. In 2013, it was first reported that PFAS could be mechanically destroyed using KOH as a co-milling agent. Subsequently, zero-valent iron, metal oxides (such as Al 2 O 3 , BaTiO 3 , La 2 O 3 , SiO 2 ), persulfate (PS), etc. have also been reported to degrade PFAS as co-milling reagents. However, the activation and subsequent cleavage of the CF bond involves the formation of thermodynamically favorable bonds to produce harmful substances such as KF, HF and fluoroacetate.

[0005] Therefore, there is a lack of a method to degrade PFAS efficiently, at low cost and without secondary pollution. Summary of the invention

[0006] In order to solve the above problems, the present invention provides a mechanochemical grinding method for efficiently degrading PFAS.

[0007] A mechanochemical grinding method for efficiently degrading PFAS comprises the following steps:

[0008] Adopt B 4 C is used as a ball milling aid, and B is mixed with C in a mass ratio of 250 to 1000:50. 4C. Put PFAS into the ball mill for grinding until B 4 The BC bond in C is broken, the CF bond in PFAS is broken, and a BF bond is formed to complete the degradation of PFAS; wherein the rotation speed of the ball mill is 300 to 600 rpm.

[0009] Note: The above method can be used to 4 The energy generated by the grinding process of C and PFAS will 4 The atoms or molecules on the surface of C are excited, and then high-energy free electrons are generated. These high-energy free electrons degrade PFAS (that is, destroy chemical bonds to obtain small molecular compounds). At the same time, the C-F bonds in PFAS are broken by high-energy free electrons, releasing F. F and B 4 The B produced by the breaking of the BC bond in C combines to form a new chemical bond to prevent F from being released into the environment and causing pollution.

[0010] Further, the grinding to B 4 The total time for the BC bond in C to break, the CF bond in PFAS to break, and the BF bond to form is 5 to 60 minutes.

[0011] Note: Experiments have shown that generally after 5 minutes of grinding, more than 60% of PFAS are rapidly degraded, and it takes 60 minutes of grinding for the concentration of PFAS to drop below the detection limit.

[0012] Further, the grinding to B 4 Methods for breaking the BC bond in C, breaking the CF bond in PFAS, and forming a BF bond include:

[0013] Within 5 minutes after starting grinding, the ball mill grinds at a rotation speed of 500 to 600 rpm;

[0014] After grinding for 5 minutes, determine whether the degradation rate of PFAS exceeds 65%. If so, change the speed of the ball mill to 300-400 rpm and continue grinding until PFAS is completely degraded. If not, continue grinding at a speed of 500-600 rpm until PFAS is degraded to 65-70%, then change the speed of the ball mill to 650-700 rpm, and continue grinding until PFAS is completely degraded.

[0015] Note: Since many PFAS are degraded after 5 minutes of grinding, if the speed of the ball mill is maintained continuously, the initial PFAS will be degraded, causing the particle size to change during the grinding process, and the contact area and reaction rate between the generated high-energy free electrons and PFAS will change. If the speed is continued, it will affect the degradation effect of PFAS.

[0016] Furthermore, the medium filling rate of the ball mill is 40-50%, and the medium includes a ball milling aid and PFAS.

[0017] Note: The above filling rate is relatively appropriate, and the degradation efficiency will decrease when it exceeds this range.

[0018] Furthermore, the ball mill is filled with N 2 , and the pressure in the ball mill is 200-300 bar.

[0019] Note: The above pressure setting can make the pressure and temperature environment in the ball mill suitable for the degradation of PFAS.

[0020] Furthermore, 4 C is powder B 4 C、Flake B 4 C and needle-shaped B 4 One or more of C.

[0021] Furthermore, the B 4 C is a powdered B with a mass ratio of 10-15:5-6 4 C and flake B 4 C, or B 4 C is a powdered B with a mass ratio of 10-15:8-10 4 C and needle-shaped B 4 C composition, wherein powdered B 4 The ratio of particle size of C to PFAS is 1:2-3, and the particle size of flake B 4 The particle size ratio of C to PFAS is 1 to 2:5.

[0022] Note: The above-mentioned shapes can improve the grinding efficiency. 4 C Mixed use can increase the contact area and collision frequency between grinding media, thereby more effectively crushing and degrading PFAS particles. 4 Due to its special shape, C can more effectively produce shearing and tearing during the grinding process, which helps to break and degrade PFAS molecules. 4 The combination of C can form a more complex grinding environment, so that PFAS particles are subjected to grinding forces of different directions and intensities, which can promote the degradation of PFAS.

[0023] Furthermore, the B 4 C is obtained through crystal modification treatment.

[0024] Further, the crystal modification treatment is:

[0025] S1. Doping with vanadium element:

[0026] 14~15gB 4 C is placed in the reaction chamber, and then heated to 800-1200°C, and a gaseous vanadium pentoxide with a flow rate of 1-3 sccm is introduced to deposit vanadium on B 4 C surface until the element vanadium doping amount is 1 to 2 g, and the deposition time is 1 to 10 h;

[0027] S2. Irradiation treatment:

[0028] A high-energy electron beam was used as the irradiation source, and the irradiation dose was set to 10 17 ions / cm 2 , B 4 C is placed in the irradiation room and irradiated for 20 to 30 minutes.

[0029] Description: B 4 C has a complex crystal structure, namely B 4 C is a boride centered on an ictohedra, B 12 The icosahedra form rhombohedral lattice units around the CBC chain at the center of the unit cell. Vanadium doping may change the B 4 The lattice parameters of C help optimize B 4 Crystal structure of C, irradiated in B 4 Introducing an appropriate amount of defects (such as point defects) into C may serve as a capture center for charges, thereby forming electric dipoles inside the material. When the material is subjected to external pressure, the arrangement of these electric dipoles changes, thus producing a piezoelectric effect. 4 Modification of the crystal structure of C can improve its piezoelectric properties and the induction of PFAS degradation during grinding, making B 4 The C surface generates charges, which further trigger the electrochemical oxidation reaction of PFAS molecules, leading to the degradation of PFAS.

[0030] The beneficial effects of the present invention are:

[0031] The present invention utilizes new ball mill B 4 C grinds and degrades PFAS, and determines the optimal material ratio, ball mill speed and ball milling time. 4 The energy generated by the grinding process of C and PFAS will 4 The atoms or molecules on the surface of C are excited, generating high-energy free electrons to degrade PFAS (i.e., destroying chemical bonds to obtain small molecule compounds). At the same time, the C-F bonds in PFAS are broken by high-energy free electrons, releasing F. F and B 4The B generated by the BC bond break in C combines to form a new chemical bond to prevent F from being released into the environment and causing pollution. The above method can achieve rapid degradation of PFAS by high-energy ball milling without the need for oxidants, high temperature and high pressure, and harmful additives, thus reducing potential harm to the environment.

[0032] Specifically, the present invention also discloses a grinding process, B 4 C. The optimization method of its own structure can make use of the friction effect (friction generates mechanical energy, which is converted into heat energy and electronic excitation energy) in the process of grinding PFAS. B. 4 The atoms or molecules on the C surface may be excited, causing electrons to jump from the valence band to the conduction band, thereby forming free electrons, triggering the electrochemical oxidation reaction of PFAS molecules and destroying the chemical bonds in PFAS molecules), interface effect (B 4 The interface between C and PFAS interacts, that is, free electrons are generated, charge transfer is carried out to complete the breaking and formation of chemical bonds, that is, the chemical bonds in PFAS molecules are destroyed) and piezoelectric effect (charge is generated, free electrons are formed, electrochemical oxidation reaction of PFAS molecules is triggered, and chemical bonds in PFAS molecules are destroyed) are destroyed to achieve efficient degradation of PFAS. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a data diagram of the PFOS degradation results of Comparative Example 1;

[0034] Figure 2 In the embodiment of the present invention, 4 The data graph of PFOS degradation efficiency corresponding to the change of C dosage;

[0035] Figure 3 is a data graph showing the degradation efficiency of PFOS corresponding to the change in the rotation speed of the ball mill in an embodiment of the present invention;

[0036] Figure 4 This is a data graph showing the degradation efficiency of PFOS corresponding to time changes in an embodiment of the present invention;

[0037] Figure 5 It is a comparison chart of the degradation efficiency results of PFOS of Example 1 of the present invention and Comparative Examples 1 to 5;

[0038] Figure 6 Is to use B 4 C is a comparison chart of the degradation efficiency results of PFOS homologues PFHxS (6S) and PFBS (4S) by grinding method;

[0039] Figure 7 DPPH and B 4 Schematic diagram of the co-grinding degradation rate of C and PFOS and the DPPH absorption peak. DETAILED DESCRIPTION

[0040] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0041] Example 1: A mechanochemical grinding method for efficiently degrading PFAS, comprising the following steps:

[0042] Adopt B 4 C is used as a ball milling aid in a mass ratio of 500:50, for example, 500 mg B 4 C: 50mgPFAS, B 4 C. Put PFAS into the ball mill for grinding until B 4 The BC bond in C is broken, the CF bond in PFAS is broken, and a BF bond is formed to complete the degradation of PFAS; wherein the rotation speed of the ball mill is 500 rpm;

[0043] The grinding to B 4 The total time for the BC bond in C to break, the CF bond in PFAS to break, and the BF bond to form is 30 min;

[0044] The ball mill has a medium filling rate of 45%; the medium includes a ball milling aid and PFAS;

[0045] The ball mill is filled with N 2 , and the pressure in the ball mill is 250 bar;

[0046] B 4 C is powder B 4 C, powdered B 4 The particle size ratio of C to PFAS is 1:2.5.

[0047] Example 2: This example is different from Example 1 in that the raw material components are different, the mass ratio is 250:50, and B 4 C. PFAS is put into a ball mill for grinding.

[0048] Example 3: This example is different from Example 1 in that the raw material components are different, the mass ratio is 1000:50, and B 4 C. PFAS is put into a ball mill for grinding.

[0049] Example 4: This example is different from Example 1 in that the rotation speed parameter is different, and the rotation speed of the ball mill is 300 rpm.

[0050] Example 5: This example is different from Example 1 in that the rotation speed parameter is different, and the rotation speed of the ball mill is 600 rpm.

[0051] Example 6: This example is different from Example 1 in that the grinding time is different, and the grinding is continued for 5 minutes.

[0052] Example 7: This example is different from Example 1 in that the grinding time is different, and the grinding is continued for 60 minutes.

[0053] Example 8: This example is different from Example 1 in that the filling parameters are different, the medium filling rate is 50%; and the pressure in the ball mill is 200 bar.

[0054] Example 9: This example is different from Example 1 in that the filling parameters are different, the medium filling rate is 40%; and the pressure in the ball mill is 300 bar.

[0055] Embodiment 10: This embodiment differs from Embodiment 1 in that B 4 The morphology of C is different, the B 4 C is made of powdered B in a mass ratio of 10:5 4 C and flake B 4 C composition, wherein powdered B 4 The particle size ratio of C to PFAS is 1:2, and the flake B 4 The particle size ratio of C to PFAS is 2:5.

[0056] Embodiment 11: This embodiment differs from Embodiment 1 in that B 4 The morphology of C is different, 4 C is made of powdered B in a mass ratio of 15:6 4 C and flake B 4 C composition, wherein powdered B 4 The particle size ratio of C to PFAS is 1:3, and the flake B 4 The particle size ratio of C to PFAS is 1:5.

[0057] Embodiment 12: This embodiment differs from Embodiment 1 in that B 4 C is made of powdered B in a mass ratio of 15:8 4 C and needle-shaped B 4 C composition, flake B 4 C or needle-shaped B 4 The particle size ratio of C to PFAS is 2:5.

[0058] Embodiment 13: This embodiment differs from Embodiment 1 in that B 4 C is composed of powdered B in a mass ratio of 10:10 4C and needle-shaped B 4 C composition, flake B 4 C or needle-shaped B 4 The particle size ratio of C to PFAS is 1:5.

[0059] Example 14: This example is different from Example 1 in that the grinding to B 4 Methods for breaking the BC bond in C, breaking the CF bond in PFAS, and forming a BF bond include:

[0060] Within 5 minutes after starting grinding, the ball mill is ground at a rotation speed of 550 rpm;

[0061] After grinding for 5 minutes, determine whether the degradation rate of PFAS exceeds 65%. If so, change the speed of the ball mill to 350 rpm and continue grinding until PFAS is completely degraded. If not, continue grinding at a speed of 550 rpm until PFAS is degraded to 68%, then change the speed of the ball mill to 680 rpm, and continue grinding until PFAS is completely degraded.

[0062] Example 15: This example is different from Example 14 in that the grinding parameters are different. Within 5 minutes after the start of grinding, the ball mill is ground at a rotation speed of 500 rpm;

[0063] After grinding, determine whether the degradation rate of PFAS exceeds 65%. If so, change the speed of the ball mill to 400 rpm and continue grinding until PFAS is completely degraded. If not, continue grinding at a speed of 500 rpm until PFAS is degraded to 70%, then change the speed of the ball mill to 700 rpm, and continue grinding until PFAS is completely degraded.

[0064] Example 16: This example is different from Example 14 in that the grinding parameters are different. Within 5 minutes after the start of grinding, the ball mill is ground at a rotation speed of 600 rpm;

[0065] After grinding, determine whether the degradation rate of PFAS exceeds 65%. If so, change the speed of the ball mill to 300 rpm and continue grinding until PFAS is completely degraded. If not, continue grinding at a speed of 600 rpm until PFAS is degraded to 65%, then change the speed of the ball mill to 650 rpm, and continue grinding until PFAS is completely degraded.

[0066] Embodiment 17: This embodiment differs from Embodiment 1 in that: 4 C is obtained through crystal modification;

[0067] The crystal modification process is:4 C is treated by doping with vanadium and then irradiated to obtain B after crystal modification. 4 C; the B 4 C is treated by doping with vanadium and then irradiated as follows:

[0068] S1. Doping with vanadium element:

[0069] 14.5gB 4 C is placed in the reaction chamber, and then heated to 1000°C, and gaseous vanadium pentoxide with a flow rate of 2sccm is introduced to deposit vanadium on B 4 C surface, deposition time is 5 h;

[0070] S2. Irradiation treatment:

[0071] A high-energy electron beam was used as the irradiation source, and the irradiation dose was set to 10 17 ions / cm 2 , B 4 C was placed in the irradiation chamber for irradiation treatment for 25 min.

[0072] Example 18: This example is different from Example 1 in that the modification treatment parameters are different, S1, doping with vanadium element:

[0073] 14gB 4 C is placed in the reaction chamber, and then heated to 800°C, and vanadium pentoxide gas is introduced at a flow rate of 1 sccm to deposit vanadium on B 4 C surface, deposition time is 1 h;

[0074] S2. Irradiation treatment:

[0075] A high-energy electron beam was used as the irradiation source, and the irradiation dose was set to 10 17 ions / cm 2 , B 4 C was placed in the irradiation room for 20 min.

[0076] Example 19: This example is different from Example 1 in that the modification treatment parameters are different, S1, doping with vanadium element:

[0077] 15gB 4 C is placed in the reaction chamber, and then heated to 1200°C, and vanadium pentoxide gas is introduced at a flow rate of 3sccm to deposit vanadium on B 4 C surface, deposition time is 10 h;

[0078] S2. Irradiation treatment:

[0079] A high-energy electron beam was used as the irradiation source, and the irradiation dose was set to 1017 ions / cm 2 , B 4 C was placed in the irradiation chamber for 30 min.

[0080] Experimental Example: This experimental example takes PFOS among PFAS as an example, and the description is based on the recorded scheme in Example 1. The specific results are as follows;

[0081] 1. To explore the effects of different treatment methods on the degradation of PFOS;

[0082] 1. Proof B 4 The effects and working principles of C;

[0083] Comparative Example 1: The difference from Example 1 is that the PFOS was ball milled alone at an initial mass of 50 mg and a rotation speed of 500 rpm;

[0084] Comparative Example 2: The difference from Example 1 is that BN is used instead of B 4 C;

[0085] Comparative Example 3: The difference from Example 1 is that SiO 2 Replace B 4 C;

[0086] Comparative Example 4: The difference from Example 1 is that KOH is used instead of B 4 C;

[0087] Comparative Example 5: The difference from Example 1 is that TiO 2 Replace B 4 C;

[0088] Comparative Example 6: The difference from Example 1 is that CaO is used instead of B 4 C;

[0089] Effect:

[0090] ①Proof B 4 C can degrade PFOS;

[0091] In the results of Comparative Example 1, PFOS was hardly degraded. Therefore, it can be seen that when only PFOS was ground, no degradation occurred. The reason may be that, without adding a medium, free electrons could not be generated to trigger the electrochemical oxidation reaction of PFOS and destroy the chemical bonds in the PFAS molecules.

[0092] The degradation of PFOS in Example 1 is as follows: Figure 1As shown in the figure, the degradation effect is good and the degradation efficiency is high. In the first 5 minutes of the reaction, PFOS was rapidly degraded by 64.8%. At the same time, the concentrations of SO42- and F- increased rapidly, indicating that in the early stage of the reaction, the instantaneous high energy of ball milling and B 4 The C co-grinding material resulted in the direct breaking of the CS and CF bonds. After 60 minutes of reaction, the concentration of PFOS dropped below the detection limit. 4 2- and F- concentrations reached peak values. It is worth noting that after 45 minutes of reaction, the desulfurization rate rose to 13.85% and remained basically unchanged, while the defluorination rate slowly decreased after reaching 23.67%. After 5 minutes of reaction, when sampling, it was observed that the powdered material was blown up from the tank by the gas, and at the same time, there was a rotten egg smell gas overflowing. Based on this experimental phenomenon and the desulfurization rate curve, it is speculated that the destination of S is SO 4 2- and SO 2 In addition, the detected F- concentration was high at first and then decreased, which can be inferred that the released F- was adsorbed by the ball-milling material.

[0093] ②Proof B 4 The degradation efficiency of C is better than other ball milling aids;

[0094] The results of PFOS degradation characteristics and defluorination rates of Comparative Examples 2, 3, 4, 5 and 6 are as follows: Figure 5 As shown by Figure 5 It can be seen that the degradation rate of Example 1 is significantly higher than that of other comparative examples;

[0095] Specifically, Figure 5 As shown in (a), the degradation rate of PFOS in Example 1 is basically complete at 30 min; while the degradation rate of PFOS in Comparative Example 2 using BN still does not reach a high degradation effect after 100 min; the degradation rates of Comparative Examples 3, 4, 5 and 6 are even lower. Therefore, although these comparative examples add media (ball milling aids), the effects of these media are very limited, and these media and B 4 C is quite different, and the working principle is also different. Some media, such as CaO, may only play a role of friction, without interface effect or other effects, and the mechanical energy generated by friction is also very limited, which cannot destroy the chemical bonds in the PFOS molecules, so the effect of the present invention cannot be achieved.

[0096] like Figure 5 As shown in (b), the reaction rate of Example 1 is also much higher than that of Comparative Examples 2, 3, 4, 5 and 6, which is consistent with B 4 The characteristics of C and B 4 C is related to the interfacial effect produced by PFOS, namely B4 There is an interaction at the interface between C and PFOS, and the specific interaction is charge transfer, breaking and forming of chemical bonds, thereby destroying the chemical bonds in the PFAS molecules.

[0097] ③Proof B 4 C can degrade a variety of PFAS;

[0098] like Figure 6 As shown in the figure, compared with PFOS, PFHxS and PFBS have two and four less -CF2- structural units in their structures, respectively. They are homologues of PFOS and belong to the perfluorosulfonic acid class of PFSAs. In the grinding parameters of Example 1, the degradation effects on PFHxS (6S) and PFBS (4S) were studied respectively, as shown in the figure. Figure 6 PFHxS (6S) and PFBS (4S) as well as Example 1 (8S) all have good effects, indicating that B 4 C has a degrading effect on a variety of PFAS.

[0099] Working principle:

[0100] Because B 4 During the ball milling process, the BC bond of C breaks, and the CF bond of PFAS is broken by high-energy free electrons to release F. The bond energy of the BF bond (644 kJ / mol) is higher than that of the CF bond (485 kJ / mol), and the binding energy of the BF bond is low, so F is "fixed" in material B. 4 C, so Figure 1 The F- concentration in the sample first increases and then decreases.

[0101] From the above content, it can be seen that the reason for destroying the chemical bonds of PFAS is the high-energy free electrons generated by multiple factors; specifically, the use of DPPH and B 4 C and perfluorooctane sulfonic acid were ground together in the manner of Example 1. The grinding results were as follows: Figure 7 As shown, DPPH was detected at 520 nm and DPPH- ions were detected at 320 nm wavelength. Since DPPH- ions are generated by DPPH absorbing electrons, this indicates that the treatment can convert DPPH into anionic state DPPH-, as shown in Figure (a). That is, the presence of DPPH anions confirms that the ball-milled PFAS of the present invention decomposes organic compounds by generating free electrons.

[0102] 2. To prove the effect of the grinding parameters and grinding method of the present invention;

[0103] Grinding parameters: including raw material ratio, ball milling speed and ball milling time;

[0104] like Figure 2 As shown, in multiple raw material ratios (i.e., multiple different B 4The degradation effect data of B under the reaction conditions of PFOS initial mass of 50 mg and rotation speed of 300 rpm. 4 The degradation efficiency of PFOS by C increases with the increase of B 4 The content of C increases with the increase of C dosage. Considering the economy and the boundary of ball milling operation, 500 mg is the best choice.

[0105] Ball mill speed:

[0106] like Figure 3 As shown in the figure, when the ball mill is in the speed range of 300 rpm to 600 rpm, the degradation efficiency of PFOS increases with the increase of the ball mill speed. Therefore, within this range, the energy input into the reaction system can be increased, thereby improving the ability of the ball milling method to degrade PFOS pollutants. However, when the ball mill speed is too fast, the effect on improving the degradation efficiency of PFOS is relatively small. For example, Figure 3 The difference between 500rpm and 600rpm is small. Considering economic factors, 500rpm should be selected.

[0107] Ball milling time:

[0108] Weigh 50 mg of PFOS and 500 mg of B 4 C was placed in a ball mill, the ball mill speed was 500 rpm, the reaction time was 5 minutes and the ball milling direction was set to on, from the beginning of the experiment to the end of the reaction, the experimental results are as follows Figure 4 As shown, the reaction is faster from 0 to 30 minutes, and the degradation is almost completed after 60 minutes. Therefore, based on the comprehensive degradation rate and treatment cost issues, the preferred range selected is 5 to 60 minutes.

[0109] Fill parameters:

[0110] Grinding operations were performed according to Example 1, Example 8 and Example 9. After 30 minutes of degradation, the result of Example 1 was 90%, while that of Example 8 and Example 9 were both lower than 90%, indicating that the medium filling rate and the pressure of the ball mill had some influence on the prosthetic joint effect. With regard to the degradation rate of PFOS, the parameters in Example 1 were more appropriate.

[0111] Grinding method: including B 4 The form of C, B 4 The structure and grinding method of C;

[0112] B 4 The form of C:

[0113] Comparative Example 7: The difference from Example 1 is that B 4 The morphology of C is all flake-like;

[0114] Comparing the degradation rates of PFOS after grinding and degradation for 30 minutes by the methods of Example 1 and Comparative Example 7, the degradation rate of the method of Comparative Example 7 after 30 minutes is 85%, which is different from that of Example 1. Therefore, the form of Example 1 is more preferred.

[0115] According to the grinding operation of Example 1, Example 10 and Example 11, when the degradation was 30 minutes, Example 10 (degradation rate was 92%) and Example 11 (degradation rate was 93%) were both higher than 90% of Example 1; this is because in Example 10 and Example 11, different shapes of B 4 C can be used in combination with grinding to improve the grinding effect, thereby increasing the degradation rate of PFOS. That is, the grinding efficiency can be improved by differentiating the shapes. 4 C mixed use can increase the contact area and collision frequency between grinding media, thereby more effectively crushing and degrading PFAS.

[0116] Grinding method:

[0117] Comparing Example 1 with Example 14, when the degradation was 30 minutes, the degradation of Example 14 was 92%, indicating that the method of Example 14 was significantly better than that of Example 1; after grinding for 5 minutes, the PFOS in Examples 1 and 14 were both degraded by 65%. In this case, reducing the speed of the ball mill was helpful for the degradation of PFOS. This is because the reaction in the first 5 minutes was more intense, and the contact area and reaction rate of the generated high-energy free electrons with PFAS changed. At this time, the speed was reduced to B. 4 C and PFOS provide a suitable interface environment, which can correspondingly improve the degradation efficiency of PFOS.

[0118] B 4 The structure of C:

[0119] Comparing Example 1 with Example 17, the degradation rate of Example 17 is as high as 95% after 30 minutes of degradation, which shows that Example 17 has a significant effect on B 4 C will be subjected to crystal modification treatment, which has an obvious effect, that is, the method of Example 17 can improve its piezoelectric properties and the induction effect on PFAS degradation during grinding, so that in B 4 The C surface generates charges, which further trigger the electrochemical oxidation reaction of PFAS molecules, leading to the degradation of PFAS.

Claims

1. A mechanochemical grinding method for efficiently degrading PFAS, characterized in that: The following steps are involved: B4C is used as a ball milling aid, and B4C and PFAS are put into a ball mill for grinding in a mass ratio of 250 to 1000:50, until the BC bond in B4C and the CF bond in PFAS are broken, and the BF bond is formed, thereby completing the degradation of PFAS; wherein the rotation speed of the ball mill is 300 to 600 rpm.

2. A mechanochemical grinding method for efficiently degrading PFAS according to claim 1, characterized in that: The total time for grinding until the BC bond in B4C is broken, the CF bond in PFAS is broken, and the BF bond is formed is 5 to 60 minutes.

3. A mechanochemical grinding method for efficiently degrading PFAS according to claim 2, characterized in that: The method of grinding until the BC bond in B4C is broken, the CF bond in PFAS is broken, and the BF bond is formed comprises: Within 5 minutes after starting grinding, the ball mill grinds at a rotation speed of 500 to 600 rpm; After grinding for 5 minutes, determine whether the degradation rate of PFAS exceeds 65%. If so, change the speed of the ball mill to 300-400 rpm and continue grinding until PFAS is completely degraded. If not, continue grinding at a speed of 500-600 rpm until PFAS is degraded to 65-70%, then change the speed of the ball mill to 650-700 rpm, and continue grinding until PFAS is completely degraded.

4. A mechanochemical grinding method for efficiently degrading PFAS according to claim 1, characterized in that: The medium filling rate of the ball mill is 40-50%, and the medium includes a ball milling aid and PFAS.

5. A mechanochemical grinding method for efficiently degrading PFAS according to claim 1, characterized in that: The ball mill is filled with N2, and the pressure in the ball mill is 200-300 bar.

6. A mechanochemical grinding method for efficiently degrading PFAS according to claim 1, characterized in that: The B4C is one or more of powdered B4C, flake B4C and needle-shaped B4C.

7. A mechanochemical grinding method for efficiently degrading PFAS according to claim 1, characterized in that: The B4C is composed of powdered B4C and flaky B4C in a mass ratio of 10-15:5-6, wherein the particle size ratio of powdered B4C and PFAS is 1:2-3, and the particle size ratio of flaky B4C and PFAS is 1-2:

5.

8. The mechanochemical grinding method for efficiently degrading PFAS according to claim 1, characterized in that: The B4C is composed of powdered B4C and needle-shaped B4C in a mass ratio of 10-15:8-10, wherein the ratio of the particle size of powdered B4C to PFAS is 1:2-3, and the ratio of the particle size of needle-shaped B4C to PFAS is 1-2:

5.

9. A mechanochemical grinding method for efficiently degrading PFAS according to claim 1, characterized in that: The B4C is obtained through crystal modification treatment.

10. A mechanochemical grinding method for efficiently degrading PFAS according to claim 9, characterized in that: The crystal modification method is: doping the surface of B4C with vanadium in a ratio of 14-15g:1-2g, and then irradiating the surface of B4C with an irradiation dose of 10 17 ions / cm 2 The irradiation time is 20 to 30 minutes to obtain B4C after crystal modification.

Citation Information

Cited By

  • Method for degrading perfluorinated and / or polyfluorinated alkyl sulfonic acid substances through mechanochemical reduction

    CN116531710A

  • Method and system for treating PFAS contaminated soil through smoldering synergistic fluorine fixation

    CN122352664A